Absorption, Translocation, and Metabolism of 14C-Halosulfuron in Grafted Eggplant and Tomato. (27th September 2017) - Chaudhari, Sushila; Jennings, Katherine M.; Monks, David W.; Jordan, David L.; Gunter, Christopher C.; Louws, Frank J.
Abstract : Grafted plants are a combination of two different interspecific or intraspecific scion and rootstock. Determination of herbicidal selectivity of the grafted plant is critical given their increased use in vegetable production. Differential absorption, translocation, and metabolism play an important role in herbicide selectivity of plant species because these processes affect the herbicide amount delivered to the site of action. Therefore, experiments were conducted to determine absorption, translocation, and metabolism of halosulfuron in grafted and non-grafted tomato and eggplant. Transplant type included non-grafted tomato cultivar Amelia, non-grafted eggplant cultivar Santana, Amelia scion grafted onto Maxifort tomato rootstock (A-Maxifort) and Santana scion grafted onto Maxifort rootstock (S-Maxifort). Plants were treated POST with commercially formulated halosulfuron at 39 g ai ha -1 followed by 14 C-halosulfuron under controlled laboratory conditions. Amount of 14 C-halosufuron was quantified in leaf wash, treated leaf, scion shoot, rootstock shoot, and root at 6, 12, 24, 48, and 96 h after treatment (HAT) using liquid scintillation spectrometry. No differences were observed between transplant types with regard to absorption and translocation of 14 C-halosulfuron. Absorption of 14 C-halosulfuron increased with time, reaching 10 and 74% of applied at 6 and 96 HAT, respectively. Translocation of 14 C-halosulfuron was limited to the treated leaf, which reached maximum (66% of applied) at 96 HAT, whereas minimal (<4% of applied) translocation occurred in scion shoot, rootstock shoot, and root. Tomato plants metabolized halosulfuron faster compared to eggplant regardless of grafting. Of the total amount of 14 C-halosulfuron absorbed into the plant, 9 to 14% remained in the form of the parent compound in tomato compared with 25 to 26% in eggplant at 48 HAT. These results indicate that grafting did not affect absorption, translocation, and metabolism of POST halosulfuron in tomato and eggplant.